Microeconometric Evaluation of Selected ESF-funded ALMP-Programmes - Eva Reinowski; Birgit Schultz (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2006)
The study evaluates different ESF-funded labour market programmes by comparing the labour market status at different points in time after the treatment. In order to solve the selection problem we employ a standard matching algorithm with a multi-dimensional distance measure. The effects of the analyzed programmes (wage subsidies, start-up subsidies and qualification measures for recipients of social welfare) are very heterogeneous. It can be observed that the direct integration into the regular labour market provides an advantage for the supported individuals. Its lasting effects, however, strongly depend on the group of persons being supported, the type of treatment and the employers' financial share. – – In der Studie werden verschiedene ESF-geförderte Arbeitsmarktprogramme über einen Vergleich des Arbeitsmarktstatus zu verschiedenen Zeitpunkten nach der Teilnahme evaluiert. Um das Selektionsproblem zu lösen, wird ein Standard-Matching-Ansatz mit einem multidimensionalen Distanzmaß genutzt. Die Wirkungen der untersuchten Programme (Einstellungszuschüsse, Existenzgründungsförderung, Qualifizierungs- und Beschäftigungsmaßnahmen für Sozialhilfeempfänger) sind unterschiedlich. Zusammenfassend kann festgestellt werden, dass die direkte Integration in den regulären Arbeitsmarkt die Beschäftigungschancen der geförderten Personen verbessert. Letztendlich hängt die Wirkung allerdings davon ab, welche Personengruppe gefördert wird, welcher Maßnahmetyp eingesetzt wird und wie hoch die finanzielle Beteiligung des Arbeitgebers ist.
urn:nbn:de:gbv:3:2-3019
Keywords: C14; J68; 330; Evaluation; Arbeitsmarktpolitik; Evaluation; Labour Market Policy